PENGGUNAAN ARANG KOMPOS PADA MEDIA TUMBUH ANAKAN MAHONI - Sri Komarayati (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
This report described results of an application of two kinds of compost charcoals on the growing media of mahoni seedlings(Swietenia rnacropbylla King)for 5-month duration. Objective of this study is to learn such applicationon the characteristics of seedlings growth.The two kinds of compost charcoals were : the one derived from tusam litters (Al) ; and the other from a mixture of litters and mahoni seeds (A.2). Results revealed that the application of compost charcoal (A1 and A2) each at 30% dosage could increase height of mahoni seedlings as much as 17.67 - 25.02 cm, which Is approximately 3 times greater than the control. The compost application also increased girth of mahoni seedling up to twice that of the controls.The application of compost charcoal at 40% dosage of either (Al) or (A2), however, showed a smaller increase in height and girth increament compared with the 30% dosage. Cummulatively,the application of compost charcoal could increase the seedling biomass by more than 400%.